How is the human microbiome linked to kidney stones? - Pei, Xin; Liu, Miao; Yu, Shanshan (Frontiers in Cellular and Infection Microbiology, 2025)
In recent years, the incidence of kidney stones has continued to rise worldwide, and conventional treatments have limited efficacy in treating stones associated with recurrent or metabolic abnormalities. The microbiome, as the ‘second genome’ of the host, is involved in the development of kidney stones through metabolic regulation, immune homeostasis and inflammatory response. Studies have shown that the urinary microbiome of healthy people is dominated by commensal bacteria such as Lactobacillus and Streptococcus, which maintain microenvironmental homeostasis, whereas patients with renal stones have a significantly reduced diversity of intestinal and urinary microbiomes, with a reduced abundance of oxalic acid-degrading bacteria (e.g., Bifidobacterium oxalicum, Bifidobacterium bifidum), and a possible concentration of pathogenic bacteria (e.g., Proteus mirabilis). The microbiome regulates stone formation through mechanisms such as metabolites (e.g., short-chain fatty acids), changes in urine physicochemical properties (e.g., elevated pH), and imbalances in the inflammatory and immune microenvironments. For example, urease-producing bacteria promote magnesium ammonium phosphate stone formation through the breakdown of urea, whereas dysbiosis of the intestinal flora increases urinary oxalic acid excretion and exacerbates the risk of calcium oxalate stones. Microbiome-based diagnostic markers (e.g., elevated abundance of Aspergillus phylum) and targeted intervention strategies (e.g., probiotic supplementation, faecal bacteria transplantation) show potential for clinical application. However, technical bottlenecks (e.g., sequencing bias in low-biomass samples), mechanistic complexity (e.g., multistrain synergism), and individual heterogeneity remain major challenges for future research. Integration of multi-omics data, development of personalised therapies and interdisciplinary research will be the core directions to decipher the relationship between microbiome and kidney stones.